Antibacterial and cellular response of piezoelectric Na0.5K0.5NbO3modified 1393 bioactive glass - Verma, A.S.; Kumar, D.; Dubey, A.K. (Elsevier Ltd, 2020)
In the present study, the combined effect of addition of varying concentrations (10–30 vol%) of biocompatible piezoelectric Na0.5K0.5NbO3 (NKN) as well as electrostatic and dynamic pulsed electrical treatment on antibacterial and cellular response of 1393 bioactive glass (1393 BG) has been examined. The phase analyses of the sintered (at 800 °C for 30 min) samples revealed the formation of 1393 BG – NKN composites without any appearance of secondary phases. The addition of 10–30 vol% NKN significantly improved the mechanical behaviour of 1393 BG like, hardness (1.7 to 2 times), fracture toughness (1.3 to 2.6 times), compressive (2.3 to 8 times) and flexural strengths (2 to 3.5 times) than monolithic 1393 BG. The piezoelectric NKN is observed to induce the antibacterial activity in 1393 BG – (10– 30 vol%) NKN composites, while Staphylococcus aureus (S. aureus, gram positive) and Escherichia coli (E. coli, gram negative) bacterial cells were exposed to unpolarized and polarized (20 kV, 500°C for 30 min) sample surfaces. The antibacterial response was examined using disc diffusion, nitro blue tetrazolium (NBT) and MTT assays. The statistical analyses revealed the significant reduction in the viability of bacterial cells on polarized 1393 BG – (10– 30 vol%) NKN composite samples. In addition, the combined effect of electrostatic and dynamic pulsed electrical stimulation (1 V/cm, 500 μs pulses) on the cellular response of 1393 BG and 1393 BG – 30 vol% NKN composites has been analysed with MG-63 osteoblast-like cells. The cell proliferation was observed to increase significantly for the dynamic pulsed electric field treated negatively charged surfaces. © 2020 Elsevier B.V.
Keywords: 1393 bioglass; Piezoelectric; Sodium potassium niobate; Antibacterial; Cellular response; e S